Separate aspects of harmonization of the labor legislation of the countries of the Eurasian Economic Union (EAEU) - J., Schramm H.; A, Tynybekov S.; A., Abikenov A.; A., Abikenov A. (Farabi Journal of Social Sciences, 2019)
At present, the labor legislation of the countries of the Eurasian Economic Union (hereinafter referred to as “the EAEU”) differs significantly from each other. The difference is observed in the approaches to the legal regulation of labor relations. The attempt to form a single market of goods, services, capital and labor resources, comprising the so-called “four freedoms” (freedom of movement of capital, goods, services and labor) on the basis of the EAEU, necessitated the approximation of national labor laws. Harmonization of the labor laws of the EAEU countries should be carried out through the development of unified labor principles based on the features of the national development of the member countries and meeting the requirements of international labor standards. At the same time, this process should not be viewed from the standpoint of unifying the national legislation, but its rapprochement. The development of legal projects and solutions, which unite and satisfy the state, will allow each state of the EAEU to retain its sovereignty and political independence, remaining subjects of international relations and international labor law. The creation and adoption of the unified labor regulatory legal act of the EAEU, the conceptual apparatus and terminology will allow to regulate, bring together and harmonize the labor legislation of these countries.